Finite cross section analysis for externally prestressed beams at ultimate flexure limit state - Lelly, Marini (2005)
This study presents the results of an analytical investigation of the strength a structural behaviour of concrete beam members prestressed with external tendons at ultimate limit state. The analysis of a beam member prestressed with external tendons that is subjected to loading up to their ultimate behaviour is more difficult than those internal bonded tendons.